Pengembangan Bahan Ajar Berbasis Digital (Flipbook) pada Materi Teknik Dasar Smash dalam Pembelajaran Sepak Takraw - Kadek Yudiawan; I Ketut Semarayasa; Ni Luh Putu Spynawati (MAN Insan Cendekia Jambi, 2026)
This study aims to produce digital-based teaching materials in the form of flipbooks on the basic smash technique material in Sepak Takraw learning. Flipbook media was chosen because it is able to combine various multimedia elements, such as text, images, videos, audio visuals, and interactive quizzes in one learning platform. The process of developing teaching materials was carried out by referring to the ADDIE model which includes five stages (Analyze, Design, Development, Implementation, and Evaluation).” Furthermore, the subjects of this study were 5th semester students of the Physical Education, Health, and Recreation Study Program, Faculty of Sports and Health, Ganesha University of Education. Product trials were conducted through individual trials involving 3 students, small group trials of 7 students, and large group trials involving 20 students. The results of the validation data analysis showed a feasibility level from material content experts of 100%, learning design experts of 87%, learning media experts of 97%, and field practitioner experts of 94%. Meanwhile, the results of the trial with students showed a feasibility percentage of 94% in individual trials, 95% in small group trials, and 89% in large group trials. Thus, the flipbook-based digital teaching material on the basic smash technique material in Sepak Takraw learning is declared to be in the very good category and very suitable for use. To the lecturers in charge of the Sepak Takraw Learning TP course, digital-based teaching materials in the form of flipbooks can be used as supporting media to facilitate the learning process, especially on the basic smash technique material.